Controllable Triboelectric Series Using Gradient Positive and Negative Charge‐Confinement Layer with Different Particle Sizes of Mesoporous Carbon Materials (Small Methods 5/2022). Issue 5 (16th May 2022) - Cha, Seokjun; Cho, Yujang; Kim, Jong Gyeong; Choi, Hyeongsub; Ahn, Dahye; Sun, Jingzhe; Kang, Dong‐soo; Pak, Chanho; Park, Jong‐Jin
Abstract : Inside Front Cover In article number 2101545, Chanho Pak, Jong‐Jin Park, and co‐workers design a three‐layer‐gradient charge confinement layer with optimized charge transport and charge confinement by synthesizing mesoporous carbon spheres with different sizes and external surface areas. After charge injection, the output voltage increased about 40 times compared to the initial value, and a high output current was achieved by additionally combining TENG and electromagnetic generator.